Qualifying classifiers and their acquisition: a review of research and practices - Glimois, Laurene (Revista Internacional de Estudios Asiáticos, 2023)
The purpose of this essay is to review the literature on numeral classifiers in Mandarin Chinese and their acquisition, in order to provide directions for future research on the acquisition of classifiers in Chinese as a second language (CSL), and inform teaching practices. This paper first defines classifiers and describes the complexity of the Chinese classifier system. The discussion then moves to an examination of studies on the acquisition of classifiers in CSL. Particular attention is given to those studies that focused on the processing of classifiers from input in CLS, because input processing, which consists in registering target linguistic features and connecting them to meaning during comprehension, is recognized across theoretical perspectives as the very first step towards second language acquisition (e.g. Ellis, 2007; Gass,1997; Krashen, 1985; Lantolf, 2000; Long, 1983; McWhinney, 1987; Robinson, 2003; Schmidt, 1990; Swain, 2005; Tomlin &Villa, 1994; VanPatten, 2015). The resulting state of the art concludes with recommendations for future research and innovation in the teaching of Chinese classifiers.